Security interventions are frequently undocumented in emergency department clinical notes. (5th March 2019) - Duncan, Jill; Brown, Nathan J; Hughes, James A; Trudgett, Scott; Crilly, Julia; Rothwell, Sean; Rosengren, David
Abstract: Objective: To compare the documentation of security interventions in ED presentations between clinical notes and security records. Methods: Presentations ( n  = 680) were randomly selected from all ED presentations to a public tertiary referral hospital in Queensland, Australia between April 2016 and August 2017 that were perceived by the treating clinician as alcohol‐related. Retrospective data, manually extracted from clinical notes and the security service database, were compared for the documentation of any security interventions. Security interventions were defined as observation without physical contact, verbal de‐escalation or physical restraint by security officers. Results: Forty‐one presentations had security interventions documented in the security services database and, of those, 20 (48.8%) had documentation in the clinical notes. Patients who required security interventions were admitted to hospital in higher proportions compared with those who did not (73.2% vs 26.8%, respectively, P  < 0.0001). Conclusion: The rate of documentation of security interventions in clinical notes was less than 50%. Documentation of critical information, including alerts and risks, in the clinical notes is an essential component of communication that the multi‐disciplinary team use to ensure patient safety. Strategies aimed at improving the documentation of security interventions in clinical notes will help to optimise risk management and the safety of patients, staff and visitors along the continuum of care.